Analisis Pengaruh Bentuk Ekor dan Kecepatan Kendaraan terhadap Performa Aerodinamis Purwarupa Kendaraan Mandalika Desantara - Sapwan Suryadi; Hendry Tira; I Gusti Ngurah Ketut Yudhyadi (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
Increased energy demand and the automotive industry in Indonesia are driving innovation in efficient vehicles through more aerodynamic designs. This study tested the aerodynamic performance of the Mandalika Desantara vehicle prototype on variations in tail shape and vehicle speed. The computational fluid dynamics simulation method was used to obtain the aerodynamic parameters. The speed variations applied were 12.33 m/s, 17.89 m/s, 23.44 m/s, and 29 m/s. The results showed that vehicles with long tails had better aerodynamics with a drag coefficient of 0.0849 and a lift coefficient of 0.0889 at a speed of 29 m/s. The low drag and lift coefficients indicated reduced drag and lift forces, thereby improving performance and maintaining vehicle stability.